Analisa Perubahan Perilaku Perawat Sebelum dan Sesudah dilakukan Pelatihan Pencegahan Phlebitis di Rumah Sakit Bunda Thamrin Medan Tahun 2022 - Jetendra P. Sihombing (Pusat Riset dan Inovasi Nasional, 2023)
. Phlebitis is the area of skin around an intravascular catheter that is swollen, red, hot and painful. The aim of this research is to find out how nurses prevent phlebitis in patients. For this research, the design used is descriptive. The population consisted of all inpatients who were placed on an IV by a nurse in the emergency room and then admitted to the hospital. Data was collected using probability sampling techniques using the Slovin formula for 69 samples, using checklists and observation sheets, and analyzed using frequency distribution. The results of research conducted on 69 nurses in the Thamrin Medan inpatient room showed that there was an increase in the actions of respondents before the training was carried out. The majority had